Innovative Activity in Wind and Solar Technology: Empirical Evidence on Knowledge Spillovers Using Patent Data - Frauke G. Braun; Jens Schmidt-Ehmcke; Petra Zloczysti (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper studies technological change in renewable energies, providing empirical evidence on the determinants of innovative activity with a special emphasis on the role of knowledge spillovers. We investigate two major renewable energy technologies-wind and solar - across a panel of 21 OECD countries over the period 1978 to 2004. Spillovers may occur at the national level, either within the same technology field or economic sector (intra-sectoral spillovers) or in related technologies or sectors (inter-sectoral spillovers), or at the international level. We find that innovation is strongly driven by knowledge spillovers, especially those occurring at the national level. Wind and solar technologies exhibit distinct innovation characteristics: both are stimulated by intra-sectoral spillovers, but respond differently to inter-sectoral spillovers, which are only influential in the case of wind technology. We also find evidence that public R&D stimulates innovation, particularly in solar technologies.
Keywords: O31; Q42; Q55; 330; Technological change; renewable energy; patents; knowledge spillover; climate change; innovation